Effect of Ethanol Extract of Mangosteen Peel on Serum Malondialdehyde and Leukotriene B4 Levels in Male White Rats (Rattus norvegicus) Wistar Strain Exposed with Electric Cigarette Smoke - Santoso, Jemima Lewi; Notopuro, Harianto; Qurnianingsih, Ema (Folia Medica Indonesiana, 2020)
This study aims to analyze the administration of mangosteen peel ethanol extract at different doses can reduce levels of malondialdehyde (MDA) and leukotriene B4 (LTB4) serum in male white rats (Rattus norvegicus) Wistar strains exposed to electric cigarette smoke. Electric cigarette induces mitochondrial ROS production and triggers oxidative stress. Antioxidants are needed by the body if there are many free radicals, for example mangosteen peel. This laboratory experimental study uses a randomized post test only control group design. Thirty male white rats were divided into 5 groups randomly (KK, KR, P1, P2, P3). KK given 0.5% Na-CMC, KR given smoke and 0.5% Na-CMC, P1, P2, P3 given smoke and mangosteen peel ethanol extract 100, 200, 300 mg / kg weight. Data were tested for normality and homogeneity tests. Data distribution was found not normal. Data were tested by Kruskal-Wallis Test and Mann-Whitney. Kruskal-Wallis Test results showed significant differences in MDA and LTB4 levels in each experimental group (KS, KR, P1, P2 and P3), p <0.05. Mann-Whitney test results showed a significant difference in the MDA levels of the KR against P3 and in the LTB4 level of the KR against P2 (p <0.05). The conclusion of the study was the administration of mangosteen peel ethanol extract can reduce MDA and LTB4 levels serum in male white rats (Rattus norvegicus) Wistar strains exposed to electric cigarette smoke.